(untitled) (Palimpsesto, 2019)
Santiago, in the Captaincy General of Chile, is the scene of a great religious controversy in the seventeenth century. The Clarisse nuns and the Franciscan prelates face each other in their search for porwer. This article reviews the aforementioned event from the "official" version contained in the stories of Vicuña Mackenna and Vicente Carvallo and the "forgotten" version documented by the nuns themselves. Paying attention to both historical sources allows us to build a more complete narrative, which overcomes that unique history of masculine tone that tends to neutralize the episode. This gender perspective reading seeks to contribute to women history and to prevail over the previous anecdote.